2020
DOI: 10.1007/s12273-020-0695-1
|View full text |Cite
|
Sign up to set email alerts
|

Indoor environment quality and work performance in “green” office buildings in the Middle East

Abstract: Globally, a primary concern is whether green office buildings perform as promised in terms of providing better indoor environment quality (IEQ) for employees, which may affect their satisfaction and work performance. In the Middle East, although there has been renewed interest in green building design, post occupancy evaluation of performance has never been conducted to-date, and evidence of actual occupant perception in green and non-green buildings is still ambiguous. Hence, we present the first study on IEQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 66 publications
(66 reference statements)
0
27
0
Order By: Relevance
“…Green buildings generally resulted in higher job satisfaction and superior individual productivity assessments when compared to conventional buildings; however, some conventional buildings outperformed some green buildings in these metrics (Newsham et al, 2017). Elnaklah et al (2020) compared green and conventional buildings in terms of various IEQ factors and found that comfort was superior in green buildings, however individual productivity was slightly higher in conventional buildings, and there was no significant difference in absenteeism and presenteeism in either building type. It was established by Lee et al (2020) that regardless of a green refurbishment or a new green building, the results were the same in IEQ user satisfaction and experienced health symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Green buildings generally resulted in higher job satisfaction and superior individual productivity assessments when compared to conventional buildings; however, some conventional buildings outperformed some green buildings in these metrics (Newsham et al, 2017). Elnaklah et al (2020) compared green and conventional buildings in terms of various IEQ factors and found that comfort was superior in green buildings, however individual productivity was slightly higher in conventional buildings, and there was no significant difference in absenteeism and presenteeism in either building type. It was established by Lee et al (2020) that regardless of a green refurbishment or a new green building, the results were the same in IEQ user satisfaction and experienced health symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Absenteeism and presenteeism are viewed as potential indicators of productivity (Roelofsen, 2002;Danielsson and Bodin, 2008;Thatcher and Milner, 2012;Agha-Hossien et al, 2013;Thatcher and Milner, 2014b;2014a;Elnaklah et al, 2020). Self-assessed productivity is another approach to determining productivity levels, where respondents were asked to rate their perceived productivity on a scale from 0-to 100% within the context of their full capacity (KPIs) (Thatcher and Milner, 2012).…”
Section: Appendixmentioning
confidence: 99%
“…After gathering the inputs of airflow matrix, ambient air pollutant level, and indoor source/sink data, the Air pollutant module calculates multizone air pollutant concentrations using the state-space method [79]. For the simulation of each air pollutant, Equation (1) can be rewritten as Equations ( 7) and (8), which are as follows:…”
Section: Diagnosis Modulementioning
confidence: 99%
“…Hence, healthy building design is an emerging need in the field of architecture and building engineering, especially in the face of increasing episodes of pandemics and climate events. The design of a healthy building requires comprehensive consideration of elements that are associated with human well-being and performance [5][6][7][8]. Among the factors, indoor air quality (IAQ) plays a crucial role in achieving healthy buildings [9].…”
Section: Introductionmentioning
confidence: 99%
“…After filtering "office building" and "English only journal articles", only 32 articles were listed. Most of these articles were related to the engineering field (21 articles) with the main focus on indoor environmental quality (see Elnaklah, Fosas, & Natarajan, 2020;Lin, Liu, Wang, Pei, & Davies, 2016) and energy consumption (see Geng, Lin, & Zhu, 2020;Yau & Lim, 2016;Zhou, Cai, & Xu, 2020). Screening of abstracts resulted in only five articles related to challenges in green office implementation with three articles focusing on developed countries (see Adomßent, Grahl, & Spira, 2019;Pulaski & Horman, 2005;Uusi-Rauva & Heikkurinen, 2013), while the rest were from China with a narrow focus on green rating (Zuo, Xia, Chen, Pullen, & Skitmore, 2016) and office interior (Gou, 2016).…”
Section: Introductionmentioning
confidence: 99%